2012
DOI: 10.5946/ce.2012.45.4.350
|View full text |Cite
|
Sign up to set email alerts
|

Ex VivoandIn VivoModels for Endoscopic Submucosal Dissection Training

Abstract: Endoscopic submucosal dissection is a technically challenging but highly effective technique for the treatment of well selected early neoplasms in the digestive tract. Although it is frequently performed in East Asian countries, the Western world has not adopted this technique yet, probably due in part to the difficulty to learn it. Ex vivo and in vivo animal models are invaluable tools to overcome at least the beginning of the learning curve, although the initial step is the acquisition of basic knowledge abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Endoscopy simulators have been shown to accelerate the learning curve in various GI endoscopic procedures, and animal models are the most commonly used type of simulator and have been shown to have a positive impact on ESD training . Due to anatomic similarities and feasibility, explanted ex vivo porcine stomachs are the most commonly used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoscopy simulators have been shown to accelerate the learning curve in various GI endoscopic procedures, and animal models are the most commonly used type of simulator and have been shown to have a positive impact on ESD training . Due to anatomic similarities and feasibility, explanted ex vivo porcine stomachs are the most commonly used.…”
Section: Methodsmentioning
confidence: 99%
“…Endoscopy simulators have been shown to accelerate the learning curve in various GI endoscopic procedures, and animal models are the most commonly used type of simulator and have been shown to have a positive impact on ESD training. 1,[10][11][12] Due to anatomic similarities and feasibility, explanted ex vivo porcine stomachs are the most commonly used. Access to fully prepared and mounted ex vivo models is now easily available in the USA through commercial vendors such as Endosim (www.endosim.com) and DeLegge (www.deleggemedical.com) which are particularly suited for training in ESD, which is technically complex and associated with a higher rate of adverse events.…”
Section: Endoscopy Simulatorsmentioning
confidence: 99%
“…It has been suggested that 10 resections in an ex vivo porcine gastric model represent an adequate experience to justify a transition to a live pig model, which provides a more realistic experience including the presence of peristalsis, intraluminal secretions, and bleeding. 95 In a study of 2 novice learners who each performed gastric ESD on 60 lesions each in an ex vivo porcine model, the total resection time, en bloc resection rate, and perforation rate all improved for both endoscopists when the last 30 resections were compared with the first 30 resections. 96 The authors calculated that the cost to train an endoscopist with 30 ex vivo gastric porcine procedures (assuming 6 lesions per stomach) would be US$8410, given the cost of the simulator used, the gastric specimens, and the disposable devices used.…”
Section: Training Modelsmentioning
confidence: 97%
“…Due to anatomical similarities and feasibility, explanted ex vivo porcine stomachs are the most commonly used. 10,33,34 Access to fully prepared and mounted ex vivo models is now easily available in the USA through commercial vendors such as EndoSim (www.endosim.com) ( Fig. 2) and DeLegge (www.deleggemedical.com) ( Fig.…”
Section: Endoscopy Simulators and Ex Vivo Modelsmentioning
confidence: 99%